Chronic Intestinal Pseudo-Obstruction and Lymphoproliferative Syndrome as a Novel Phenotype Associated With Tetratricopeptide Repeat Domain 7A Deficiency - El-Daher, Marie-Thérèse; Lemale, Julie; Bruneau, Julie; Leveau, Claire; Guerin, Frédéric; Lambert, Nathalie; Diana, Jean-Sébastien; Neven, Bénédicte; Sepulveda, Fernando E.; Coulomb-L'Hermine, Aurore; Molina, Thierry; Picard, Capucine; et al. (Frontiers in Immunology, 2019)
Mutations in the tetratricopeptide repeat domain 7A (TTC7A) gene cause very early onset inflammatory bowel diseases (VOIBD) or multiple intestinal atresia associated with immune deficiency of various severities, ranging from combined immune deficiency to mild lymphopenia. In this manuscript, we report the clinical, biological and molecular features of a patient born from consanguineous parents, presenting with recurrent lymphoproliferative syndrome and hypergammaglobulinemia associated with chronic intestinal pseudo obstruction (CIPO). Genetic screening revealed the novel c.974G>A (p.R325Q) mutation in homozygosity in the TTC7A gene. The patient’s phenotype differs significantly from that previously associated with TTC7A deficiency in humans. It becomes closer to the one reported in the ttc7a-deficient mice that invariably develop a proliferative lymphoid and myeloid disorder. Functional studies showed that the extreme variability in the clinical phenotype couldn’t be explained by the cellular phenotype. Indeed, the patient’s TTC7A mutation, as well as the murine-ttc7 mutant, have the same functional impact on protein expression, DNA instability and chromatin compaction, as the other mutations that lead to classical TTC7A-associated phenotypes. Given TTC7A’s scaffolding properties, we suggest each mutant can differentially alter specific protein-protein interactions, leading to differences between the patients’ phenotypes. The present case report shows that the clinical spectrum of TTC7A deficiency is much broader than previously suspected. Our findings should alert the physicians to consider screening of TTC7A mutations in patients with lymphoproliferative syndrome and hypergammaglobulinemia and/or chronic intestinal pseudo-obstruction.